Draught work efficiency of F1 crossbred dairy cows and the Ethiopian highland Zebu oxen under smallholder farming context - Alemayehu, M.; Zerbini, E.; Yami, A. (Ethiopian Society of Animal Production, 2000)
Draught animals are the main integrative links between crop and livestock production systems in the highlands of Ethiopia. The highlands comprise only 40% of the country's total land area but carry 79% of livestock heads and 80% of the human population results in higher pressure on the arable land and feed resources. The use of crossbred dairy cows for both milk production and draught is one possible alternative option to intense the farming systems in the region and make more efficient use of the limited farm resources. The present study was carried out to compare the on farm draught performance of F1, crossbred dairy cows with that of local oxen. Thirty-six F1 crossbred dairy cows were distributed to 18 farmers of three categories of defined resource endowment in 1995 in Wolmera and Dendi woredas. Similarly, 36 local oxen were randomly selected from another 18 farmers of three resource endowment categories. Draught performance parameters include force (N), speed (m/sec),distance traveled (m), power output (kW), work output (MJ), energy expenditure (MJ) and area cultivated (m2) were studied in 1996 ploughing season for F1 crossbred cows and zebu oxen. Crossbred cows and local oxen exerted similar horizontal draught force that averaged 736 N but sustained it at different level of pull. Crossbred cows worked at a speed which was 0.16 m/s faster than that of local oxen and generated 107 W more power. Area ploughed and total net energy expended by crossbred cows over one hour period was significantly larger than that of local oxen. Local oxen required 12% more metabolizable energy per Kg W 0. 75 compared to crossbred cows for ploughing one m2 area of land. This might indicate that crossbred cows utilize metabolizable energy more efficiently for ploughing. This study has revealed that crossbred cows have a promising potential to perform ploughing activities and can complement or substitute oxen for this purpose.